Serological investigation of vaccine-induced antibodies for measles, rubella, and yellow fever viruses in children vertically exposed to Zika virus or with down syndrome - Familiar-Macedo, Débora; Dias, Helver Gonçalves; Carvalho, Fabiana Rabe; Pauvolid-Corrêa, Alex; da Silveira, Mayara Neto; Oliveira, Mariana Cavalcante de; Gonçalves, Rita de Cássia Ferreira; Vianna, Renata Artimos de Oliveira; Cardoso, Claudete Aparecida Araujo; Boy da Silva, Raquel Tavares; Baumblatt, Anna Paula; de-Oliveira-Pinto, Luzia Maria (Frontiers in Pediatrics, 2023)
Vaccination schedules, as well as their effectiveness and contraindications, need to be evaluated regularly, especially in specific situations. Congenital Zika Syndrome (CZS) is a severe condition that results in extensive functional and neurological impairment of fetuses and newborns due to Zika virus tropism for fetal neural progenitor cells. Down Syndrome (DS) is the leading genetic cause of intellectual disability. The immune impairment in DS has already been described, but little is known about the immune response of CZS children. Thus, CZS and DS are specific conditions which can be considered for reassessment of the available immunizations. Here, we carried out serological analyses of attenuated vaccines-induced antibodies for measles, rubella, and yellow fever viruses in children aged two to seven, grouped into three categories: asymptomatic controls, DS children, and CZS children. Plasma samples were taken, and vaccination records were compiled during clinical follow-up. Enzymatic immunoassays for quantifying anti-measles and anti-rubella IgG were performed to assess the response to the Measles, Mumps, and Rubella (MMR) vaccine. The Plaque Reduction Neutralization Test (PRNT) was performed to investigate neutralizing antibodies in response to the Brazilian vaccine strain of yellow fever (YF-17DD). We highlight similar levels of antimeasles IgG and neutralizing antibodies for YF-17DD among CZS, DS, and asymptomatic children, although low positivity of measles data were seen in the three groups. In DS children, the two to four-year-old group had an increased level of anti-measles IgG compared to the older group of children aged five to seven years. Lower anti-rubella IgG levels were observed in CZS and DS children compared to asymptomatic children. For anti-rubella IgG, the good performance of vaccination in asymptomatic children is due to younger ones rather than older ones. There were no reports of adverse events after the use of the MMR and YF-17DD indicating that CZS and DS could continue to receive these vaccines, but our data draws attention to the necessity of monitoring the vaccination response in CZS and DS children over time and the possible need to adhere to national measles vaccination campaigns. Scientific research needs to continue to help develop appropriate CZS and DS health guidelines.